Legal Reasoning Pada Perkara Pengujian Undang-Undang (Studi Perbandingan) - Hardjaloka, Loura (Jurnal Konstitusi, 2015)
Article 24 C of Third Amendment of Constitution Law 1945 is the basis of the Constitutional Court to give the final and binding decision in terms of law examination against Constitution Law 1945. Constitutional Court has a restriction to not examine the nebis in idem case unless there is a different substance of Constitutional Law 1945 which is used as the based of examination. In this paper, there are 12 (twelve) Constitutional Court’s decisions on law re-examination against the Constitutional Law 1945 because using different substance of Constitutional Law 1945 as the based of examination. Based on the research, which has been conducted, there are legal reasoning differences in accepting and deciding the cases which have been decided previously which the Court  uses  different  legal  interpretation  and  construction in deciding the case. Thus, this paper will examine and compare legal reasoning methods which are used in deciding the case.